The Development of Foreign Exchange Market Trends During the Period of Global Systemic Changes (European Journal of Economics, Finance and Business Development, 2023)
In the current period of instability, it can lead to the economic collapse of world countries. Due to these challenges, trade relations are broken, needed to search for new logistics centres for exporting products, problems with money transfers and the difficulties caused by the expansion of migration have increased in Central Asia, Caucasus and the Baltic countries. As a result, the price of raw materials will rise, the real income of the population will decrease, and as a result of the reduction of entrepreneurship, the dynamics of the currency exchange rate will increase. The changes will lead to instability in the currency market as well. The article is devoted to the analysis of these issues based on the data of the International Monetary Fund.